Traditional Chinese medicine injections with Tonifying Qi, equivalent effect of regulating energy metabolism, for acute myocardial infarction: a systematic review and meta-analysis of randomized clinical trials - Zhou, Huiwen; Chen, Jiaping; Liu, Hongxu; Li, Xiang; Zong, Huiqi; Zhang, Shuwen; Shi, Yuxin; Li, Yunze (Frontiers in Pharmacology, 2025)
BackgroundTraditional Chinese medicine injections for Tonifying Qi (TCMi-TQs), which exhibits comparable effect of regulating energy metabolism, is commonly used as an adjuvant treatment for acute myocardial infarction (AMI) in China.ObjectiveA systematic review and meta-analysis was conducted to contrast the effectiveness and safety of four TCMi-TQs in AMI.MethodsEight Databases were thoroughly searched before 31 July 2024, for randomized controlled trials (RCTs) focusing on the application of TCMi-TQs combined with conventional treatments (CT) to treat AMI. The primary outcomes were in-hospital mortality and long-term mortality. Secondary outcomes included malignant arrhythmia, left ventricular ejection fraction (LVEF), and adverse events. Stata17.0 and RevMan 5.4.1 software were employed for meta-analysis. The quality of evidence was evaluated using the GRADE approach.ResultsA total of 113 RCTs involving 10,779 patients were included in the analysis, none of which described in-dependent testing of the purity or potency of the TCMi-TQ product used. 51/113 reported random sequence generation. All RCTs lack adequate description of allocation concealment. 112/113 failed to assess blinding. The meta-analysis results demonstrated that the combined application of TCMi-TQ + CT, compared with CT, significantly reduced in-hospital mortality in AMI patients [RR = 0.58, 95% CI (0.51, 0.67), P < 0.05], decreased the incidence of malignant arrhythmia [RR = 0.51, 95%CI(0.42, 0.63), P < 0.05], increased LVEF [MD = 6.52, 95%CI(5.54, 7.50), P < 0.05], and decreased the incidence of adverse events [RR = 0.70, 95%CI(0.60, 0.81), P < 0.05]. The GRADE evidence quality classification indicated that the evidence for in-hospital mortality, malignant arrhythmia, and adverse events was of moderate quality, while the evidence for LVEF was of low quality.ConclusionTCMi-TQ demonstrates additional clinical value in reducing mortality, the risk of malignant arrhythmia, and adverse events in patients with AMI. However, further validation of these findings is warranted through high-quality clinical trials due to methodological weaknesses in randomization, blinding, allocation concealment, and insufficient assessment of the purity/potency of botanical drugs and the quantity of active metabolites.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024573818, identifier PROSPERO (CRD42024573818).